2012
DOI: 10.2134/agronj2011.0374
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Weed Suppression of Crop Mixtures in Organic and Conventional Systems of the Western Canadian Prairie

Abstract: To investigate intercropping as a management strategy to increase crop productivity and weed suppression in organic systems, spring wheat (Triticum aestivum L.), barley (Hordeum vulgare L.), canola (Brassica napus L.) and fi eld pea (Pisum sativum L.) monocultures were compared with two-, three-, and four-crop intercrops containing wheat at two organic and one conventional site in 2006 and 2007, central Alberta, Canada. We measured crop and weed biomass, grain yield, and crop competitiveness against weeds from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…This is likely due to the declining carbohydrate reserves of nondormant cuttings later in the season. However, as WSA and WT are simple proportions between biomass of crop (in our case willow) and weed (in our case spring barley) grown in mixtures and in monocultures [25,26], levels of WSA and WT also may be influenced by other factors than direct cropweed interactions. Influence of organisms from other tropic ) from non-dormant and dormant willow cuttings grown with and without weeds planted at five different dates.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the declining carbohydrate reserves of nondormant cuttings later in the season. However, as WSA and WT are simple proportions between biomass of crop (in our case willow) and weed (in our case spring barley) grown in mixtures and in monocultures [25,26], levels of WSA and WT also may be influenced by other factors than direct cropweed interactions. Influence of organisms from other tropic ) from non-dormant and dormant willow cuttings grown with and without weeds planted at five different dates.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited documented research work on grain intercropping in the NGP and the results of this research are inconsistent. Overyielding and greater yield stability have been observed in some crop combinations and under some conditions, but not in others (Carr et al 1995(Carr et al , 2004Szumigalski and van Acker 2005;Kaut et al 2008;Pridham and Entz 2008;Hummel et al 2009;Nelson et al 2012).…”
Section: Annual Polyculturementioning
confidence: 95%
“…In spite of a lack of clear evidence for increased yield, many studies report other benefits such as weed suppression (Carr et al 1995;Szumigalski and van Acker 2005;Pridham and Entz 2008;Nelson et al 2012), lower levels of plant disease (Vilich-Meller 1992;Jensen et al 2005;Pridham and Entz 2008;Hummel et al 2009), enhanced nutrient cycling (Szumigalski and van Acker 2006), and enhanced seed quality (Hummel et al 2009). Positive effects of intercropping on insect populations have not been observed in research from the prairie region (Weiss et al 1994;Butts et al 2003;Hummel et al 2009).…”
Section: Annual Polyculturementioning
confidence: 99%
“…Several studies have shown that intercropping reduces wealth, infestation, density and growth of weeds in relation to monocropping (Ibeawuchi et al, 2005;Agegnehu et al, 2008;Nelson et al, 2012). In some of these studies, intercropping has provided economic benefit and weed control (Agegnehu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, intercropping has provided economic benefit and weed control (Agegnehu et al, 2008). In others, there was a reduction of the infestation, but there was no benefit of intercropping in relation to monocropping (Nelson et al, 2012). Ibeawuchi et al (2005) have found that the most productive intercroppings were the ones that least controlled weeds and vice versa.…”
Section: Introductionmentioning
confidence: 99%